Large Modulus Method to Effectively Relieve Trapped-oil Phenomenon for Gear-pump and Gear-motor with Equal Displacement - Liu Ping; Li Yulong; Song Anran (Jixie chuandong)
In order to effectively relieve the trapped-oil phenomenon of external gear-pumps and gear-motors, based on its constant output capacity, by analyzing the influence of large modulus under equal displacement on the load flow, leakage flow and unloading flow in trapped-oil chamber, a design method of large modulus with equal displacement is proposed. Based on the instantaneous balance of these three flows, and the deductive calculation of the unloading area under different modules with the same tooth profile parameters, the trapped-oil pressure is calculated and the relief degree of the trapped-oil phenomenon is judged. The results show that the tooth width coefficient under equal displacement is inversely proportional to the third power of the modulus for a given gear-pairs and working conditions, the larger the modulus is, the more the trapped-oil phenomenon tends to be relieved, and the smaller the radial force is, the smaller the tooth width coefficient will be. The unloading area under different modules and the same tooth shape parameter is equal to the module square multiplied by the unloading area under the reference module of 1, which provides great convenience for calculating the unloading area under different modules with the same tooth profile parameters.The inlet and outlet pressures outside the unloading groove are reversed, leading to a more serious trapped-oil phenomenon in the gear-pump than in the gear-motor, but the small modulus motor also shows more serious trapped-oil phenomenon. It is concluded that the maximized or larger modules is included in the gear-pump and gear-motor design criteria.